Methodological instructions for the performance of control works in the academic discipline "Financial security and financial risks" - Yurieva, Iryna (National Technical University "Kharkiv Polytechnic Institute", 2024)
The purpose of studying the discipline is the formation of a knowledge system on the issues of ensuring financial security and financial risks as a component of economic and national security, as well as those functional elements that directly affect the level of development of the state's economic system in the conditions of global transformations. As a result of studying the discipline "Financial security and financial risks," students should not only master the basics of the theory of economic and financial security and financial risks but also learn to evaluate the economic processes taking place in society objectively, navigate in the information space, thoroughly analyze and understand the problems and trends in the development of the country's financial system.
Keywords: methodological instructions; economic activity; finance; risks; audit; management